Research Of Insurance Terms in Linguistics - Khaydarov Ilhom Tukhtaevich (Genius Journals, 2022)
The article focuses on research analysis of the insurance sector in English, Uzbek and Russian, origin of insurance terms, formation, conceptual and methodological features
Keywords: terminology; insurance; word origin; word formation